Literature Review of The Influence of Tax Service Quality and Tax System Modernization on Taxpayer Compliance By Moderating On Taxpayer Satisfaction - Alya Syafikah Rani; Tutty Nuryati; Tri Yulaeli; Betti Nurbaiti; Endah Prawestiningrum (Sean Institute, 2025)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomenon of the relationship or influence between variables. This article reviews the factors that influence taxpayer compliance, namely the quality of tax services and modernization of the tax system and tests the role of taxpayer satisfaction as a moderating variable in a tax accounting literature study. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) The quality of tax services affects taxpayer compliance; 2) System modernization affects taxpayer compliance; 3) Taxpayer satisfaction strengthens the influence of the quality of tax services on taxpayer compliance; 4) Taxpayer satisfaction strengthens the influence of tax system modernization on taxpayer compliance.